(untitled) (International Journal of Physiotherapy, 2016)
Background: Plantar fasciitis (PF) is the most common cause of heel pain and it can often be a challenge for clinicians to treat successfully. Radial shock wave therapy (RSWT) has been introduced recently for treatment of musculoskeletal disorders. Different energy levels of shock wave therapy have been used in the literatures for treatment of PF with no clear settled parameters. Therefore, the purpose of this study was intended to investigate and compare the efficacy of two different energy levels of RSWT on PF patients. Methods: Forty patients having unilateral chronic PF were recruited for the study from orthopedic outpatient clinics of Cairo University hospitals and National Institute of Neuromotor System Cairo Egypt, with a mean age of (47.15±4.57) years. Patients were randomly assigned into two equal groups. Group (A) treated with low intensity level of 1.6 bars (0.16 mJ/mm2) RSWT and group (B) treated with medium intensity level of 4 bars (0.38 mJ/mm2) RSWT. Functional assessment of the foot based on Foot Function Index (FFI) and Present pain intensity was measured during rest by Visual Analogue Scale (VAS). Results: There was as significant decreased in the total FFI scores from (118.42 ±6.51) to (81.37 ±3.46) for group (A) and from (118.93 ±6.85) to (58.50 ±3.22) for group (B). Also regarding VAS Scores there was as significant decreased in the pain intensity from (5.11 ±0.41) to (2.85 ±0.31) for group (A) and from (4.95 ±0.39) to (2.05 ±0.22) for group (B). Conclusion: Radial shock wave therapy is an effective modality that should be considered in the treatment of chronic PF, while the medium energy level RSWT is better than the low energy level RSWT in regarding to the measured treatment outcomes.